Economic Valuation of the Mangrove Ecosystem in Banua Pangka, Bawalipu Village, Wotu District, East Luwu Regency - Firiah Fatmaridha; Hamzah Tahang; Amiluddin Amiluddin; Muhammad Dalvi Mustafa; Kasri Kasri; Aris Baso (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2026)
This study aims to analyze the economic value of the mangrove ecosystem in Banua Pangka, Bawalipu Village, Wotu Subdistrict, East Luwu Regency. The study was conducted from January to February 2025. The research employed a survey method, involving field observations and face-to-face interviews with respondents, as well as the use of questionnaires as data collection tools. There are four types of potential and utilization in Banua Pangka: direct benefits (fish, crabs), indirect benefits such as erosion control, ecotourism and carbon sequestration, presence value, and option value. The total economic value of the mangrove ecosystem in Banua Pangka consists of direct benefits of Rp. 762,850,000, indirect benefits amounting to Rp. 2,657,005,488, choice value of Rp. 3,682,125, and existence value of Rp. 680,000; thus, the total value of the mangrove ecosystem amounts to Rp. 3,424,217,613. These results indicate that the local community is highly dependent on the mangrove ecosystem and understands the functions and roles of mangroves as an economic ecosystem and as a barrier against coastal erosion.